Influence of chemical treatment on tensile strength, water absorption, surface morphology, and thermal analysis of areca sheath fibers. Issue 4 (19th May 2019) - Nayak, Subhakanta; Mohanty, Jyoti Ranjan
ABSTRACT: Proper surface modification is highly essential to improve compatibility of natural fibers with polymer matrix to develop eco-friendly materials. In the present work, an attempt has been made to study the effect of various chemical treatments such as alkaline, acrylic acid, permanganate, sodium chlorite, and benzoylation on areca sheath fiber. After surface modifications, its density, water absorption property, mechanical property, thermal gravimetry analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and surface morphology have been thoroughly investigated. It has been observed that benzoyl chloride-treated fiber gives better performance in comparison to other treatments.